A magneto-controlled microfluidic device for voltammetric immunoassay of carbohydrate antigen-125 with silver–polypyrrole nanotags. Issue 34 (17th August 2020) - Huang, Jiyi; Huang, Chaoqun; Zhong, Weimin; Lin, Yao
Abstract : An innovative magnetic immunoassay was developed for the voltammetric detection of carbohydrate antigen-125 on a home-made microfluidic device including a multisyringe pump, selection valve and magneto-controlled detection cell. Abstract : An innovative magnetic immunoassay was developed for the voltammetric detection of carbohydrate antigen-125 (CA-125) on a home-made microfluidic device including a multisyringe pump, selection valve and magneto-controlled detection cell. Two kinds of biofunctionalized nanostructures including anti-CA-125 capture antibody-conjugated magnetic beads and anti-CA-125 detection antibody-labeled silver–polypyrrole (Ag–PPy) nanohybrids were utilized for a sandwiched immunoreaction in the presence of CA-125. With the help of an external magnet, the formed magnetic immunocomplexes were attached to the sensing interface to activate the electrical contact between Ag–PPy nanohybrids and the base electrode, thus resulting in the switching on of the sensor circuit for the generation of voltammetric signals thanks to electroactive Ag–PPy nanohybrids. Compared to silver nanoparticles (AgNPs) alone, improved analytical properties were acquired with Ag–PPy nanohybrids. Under the optimal conditions, the currents depended on the concentrations of target CA-125, and exhibited a linear relationship within the ranges of 0.001–300 U mL −1 at a detection limit of 7.6 mU mL −1 . For the determination of CA-125, the magnetic immunoassay had acceptable reproducibility, high specificity against other biomarkers and long-term storage stability. Moreover, good accuracy was obtained for the CA-125 detection in human serum samples with the developed voltammetric immunoassay relative to commercial enzyme-linked immunosorbent assay (ELISA). Importantly, the magneto-controlled immunosensing interface could be repeatedly used via detaching/attaching the external magnet.